Life changes, self-prevention, knowledge and mental health among inflammatory bowel disease patients during COVID-19 pandemic: a cross-sectional study - He, Shiwen; Xiao, Tao; Xia, Yingchun (Frontiers in Public Health, 2024)
Background: With the COVID-19 pandemic going to be COVID-19 endemic, the negative impact of COVID-19 on the mental health of IBD patients cannot be ignored.This study aimed to investigate the occurrence of anxiety and depression in IBD patients during the COVID-19 pandemic and analyze the factors associated with mental health.Methods: Patients registered at the IBD center were enrolled. Electronic questionnaires about the IBD patient's demographic information, basic knowledge of COVID-19, public self-prevention measures, daily life changes, and anxiety and depression were distributed.Results: 215 IBD patients finished this study and reported to have anxiety (27%) or depression (34%). During the COVID-19 pandemic, 10.2% of IBD patients reported their diet changes, 58.5% of IBD patients changed their daily physical activities from 3.27 ±3.252 hours to 2.30 ±2.78 hours, 33.7% of IBD patients changed their sleeping duration from 7.99 ±1.322 hours to 8.18±1.447 hours. IBD patients' waiting time for admission (OR:3.688, 95%CI:1.003-13.554), regularly oral medicine administration (OR:18.407, 95%CI:1.975-171.530) and diet changes (OR:6.167, 95%CI:2.158-17.626) were positively correlated with anxiety or depression. IBD patients' timely periodic infusion of biological agents (OR:0.586, 95%CI:0.413-0.830) was negatively correlated with anxiety or depression. IBD patients' knowledge of COVID-19, public self-prevention, physical activities, and sleep duration changes showed no significant correlation with anxiety and depression, all P values>0.05.The main factors of IBD patients' mental health were diet changes, waiting time for admission, taking oral medicine regularly, and timely periodic infusions of biological agents. Ensuring the supply of routine treatment and medication for IBD patients and establishing systemic online IBD self-management programs would be the focus of major public health events.